Gravity and magnetic exploration : principles, practices, and applications - Hinze, William J.; Von Frese, R.; Saad, Afif H.; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
This combination of textbook and reference manual provides a comprehensive account of gravity and magnetic methods for exploring the subsurface using surface, marine, airborne and satellite measurements. It describes key current topics and techniques, physical properties of rocks and other earth materials, and digital data analysis methods used to process and interpret anomalies for subsurface information. Each chapter starts with an overview and concludes by listing key concepts to consolidate new learning. An accompanying website presents problem sets and interactive computer-based exercises, providing hands-on experience of processing, modeling and interpreting data. A comprehensive online suite of full-color case histories illustrates the practical utility of modern gravity and magnetic surveys. This is an ideal text for advanced undergraduate and graduate courses and reference text for research academics and professional geophysicists. It is a valuable resource for all those interested in petroleum, engineering, mineral, environmental, geological and archeological exploration of the lithosphere.
Machine generated contents note: Preface; Acknowledgements; 1. Introduction; Part I. Gravity Exploration: 2. The gravity method; 3. Gravity potential theory; 4. Density of Earth materials; 5. Gravity data acquisition; 6. Gravity data processing; 7. Gravity anomaly interpretation; Part II. Magnetic Exploration: 8. The magnetic method; 9. Magnetic potential theory; 10. Magnetization of Earth materials; 11. Magnetic data acquisition; 12. Magnetic data processing; 13. Magnetic anomaly interpretation; Part III. Applications: 14. Applications of the gravity and magnetic methods; Appendix A. Data systems processing; References; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Geomagnetism; Magnetic measurements; Gravity -- Measurement; Electronic books